2006
DOI: 10.1117/12.680824
|View full text |Cite
|
Sign up to set email alerts
|

Broadband backhaul communication for stratospheric platforms: the stratospheric optical payload experiment (STROPEX)

Abstract: A high bitrate optical downlink was performed by the stratospheric optical payload experiment (STROPEX), a part of the EU CAPANINA project. The STROPEX objectives were to design and build the necessary hardware to demonstrate an optical backhaul downlink from a stratospheric platform to the ground and to carry out channel measurements on the link. A successful measurement campaign at ESRANGE near Kiruna, Sweden achieved all of these objectives. The transportable optical ground station received an almost error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…For example, the DLR Capanina Trial 2 weather balloon used a Microair T2000 transponder. This transponder cost $2,300 and weighed 0.6 kg [1]. For a slightly higher price and weight, the Filser TRT800 could have been used that had the capability to transmit ADS-B information.…”
Section: Automatic Dependent Surveillance-broadcastmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the DLR Capanina Trial 2 weather balloon used a Microair T2000 transponder. This transponder cost $2,300 and weighed 0.6 kg [1]. For a slightly higher price and weight, the Filser TRT800 could have been used that had the capability to transmit ADS-B information.…”
Section: Automatic Dependent Surveillance-broadcastmentioning
confidence: 99%
“…Low cost off-the-shelf receivers can be used and their accuracy is ever increasing. Europe is currently developing the Galileo Global Navigation Satellite System which, according to a 2004 agreement between the United States and the European Union, will be fully compatible and interoperable with GPS [1]. This promises increased integrity and accuracy of GNSS solutions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the Capanina STROPEX trial it has been shown that it is possible to use only GPS positions of the counter terminal, transmitted via signaling link, for acquisition of a partner terminal [1]. The duration for an acquisition or a reacquisition run during this trial was up to 20 seconds and whenever the line of sight had been blocked, the Capanina terminal had to do a reacquisition of the counter terminal.…”
Section: Introductionmentioning
confidence: 99%
“…Details on the flight system including the flight trajectory can be found in [2]. Results of the atmospheric measurements will be presented in Section 4.…”
Section: Introductionmentioning
confidence: 99%